Genetic Diversity Studies Based on Morphological Variability, Pathogenicity and Molecular Phylogeny of the Sclerotinia sclerotiorum Population From Indian Mustard (Brassica juncea) - Sharma, Pankaj; Samkumar, Amos; Rao, Mahesh; Singh, Vijay V.; Prasad, Lakshman; Mishra, Dwijesh C.; Bhattacharya, Ramcharan; Gupta, Navin C. (Frontiers in Microbiology, 2018)
White mold or stem rot disease are ubiquitously distributed throughout the world and the causal organism of this disease Sclerotinia sclerotiorum (Lib.) de Bary, is known to infect over 400 plant species. Sclerotinia stem rot is one of the most devastating fungal diseases and poses a serious threat to the worldwide cultivation of oilseed Brassica including India. S. sclerotiorum pathogen usually infects the stem but in severe cases leaves and pods also affected at different developmental stages that deteriorate not only the oil quality but also causing the seed and oil yield losses up to 90% depending on the severity of the disease infestation. This study investigated the morphological and molecular characterization of pathogenic S. sclerotiorum (Lib) de Bary geographical isolates from oilseed Brassica including B. juncea (Indian mustard). In this study, Sclerotinia isolates were collected from cultivated Brassica species from ten different Indian states to determine the pathogen diversity and examine the virulence of this pathogen specifically in Brassica for the first time. The collection of S. sclerotiorum pathogen from symptomatic Brassica plants was identified and analyzed by morphological features, physical appearance, and molecular characterization. The virulence evaluation test of 65 isolates on four Brassica cultivars has shown 5 of them were highly virulent, 46 were virulent and 14 were moderately virulent. Phylogenetic analysis encompassing all the morphological features, SSR polymorphism, and ITS sequencing has shown the existence of high genetic diversity among the isolates that categorized all the isolates in three evolutionary lineages in the derived dendrogram. Further, genetic variability analysis based on sequences variation in ITS region of all the isolates has shown the existence of either insertions or deletions of the nucleotides in the ITS region has led to the interspecies variability and observed the variation were in a clade-specific manner. Together this analysis observed the existence of higher heterogeneity and genetic variability in S. sclerotiorum isolates collection and indicates the presence of clonal and sexual progenies of the pathogen in the mustard growing regions of India surveyed in this study. With a higher level of genetic variability and diversity among the S. sclerotiorum population needs